Comparative Analysis of Machine Learning Models for Emotion Classification in Textual Data - Gregorius Airlangga (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
This research presents a comprehensive comparative analysis of various machine learning models for emotion classification within textual data, aiming to identify the most effective architectures for understanding and interpreting emotional undertones. With the increasing prevalence of digital communications, the ability to accurately classify emotions in text has significant implications across numerous domains, including social media analysis, customer service, and mental health monitoring. This study evaluates traditional algorithms, such as Logistic Regression, and advanced deep learning models, including Long Short-Term Memory (LSTM), Gated Recurrent Units (GRU), Convolutional Neural Networks combined with Recurrent Neural Networks (CNN-RNN), Autoencoders, and Transformers. Through meticulous cross-validation, hyperparameter tuning, and performance evaluation based on accuracy, precision, recall, and F1 scores, the research elucidates the strengths and weaknesses of each model. LSTM and GRU models demonstrated superior performance, highlighting the importance of sequential data processing capabilities. In contrast, the Autoencoder model underperformed, underscoring the necessity for careful model selection tailored to the task's specifics. Surprisingly, Logistic Regression showed notable efficacy, advocating for its potential utility in scenarios prioritizing computational efficiency. This study enhances the understanding of affective computing within natural language processing, offering insights into the strategic deployment of machine learning models for emotion recognition and paving the way for future advancements in the field.